Distribution of Gypsum Deposits in Bikaner District (Rajasthan): Exploration and Utilization of Gypsum Deposits in Bikaner District (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Gypsum is a valuable mineral geologically gypsum of Bikaner district belongs to thePleistocene to recent formula which is mostly gypsite type and occur in a bedded form. Gypsum is widelyused for plastering building in towns and rural areas and also as bricks of lawn and secondly used asfertilizers. In Bikaner district gypsum bearing areas are confined 30-40km for Bikaner City like Jambar,Allah -Din-ka-Bela, Hansuwali, Nawshra, Balahar, KANVNI etc.